2016
DOI: 10.1111/rda.12836
|View full text |Cite
|
Sign up to set email alerts
|

Research on reproduction is essential for captive breeding of endangered carnivore species

Abstract: Assisted reproductive technology (ART) has great potential for conservation, but its successful application in captive breeding programmes of endangered species is often compromised by limited background on species' biology. Although carnivore species benefit from knowledge obtained in domesticated species (dogs, cats and ferrets), the focus of research is different. In pet animals, research in reproduction has mainly been focused on ovarian function and contraception, although substantial progress has also be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 50 publications
0
15
0
2
Order By: Relevance
“…Consequently, there has been a historical gap between the study of cryopreservation technologies and its applications for wildlife conservation (reviewed in Holt, 2008;Jewgenow, Braun, Dehnhard, Zahmel, & Goeritz, 2017). While gamete cryopreservation studies regularly cite their potential use for species conservation, few have shown the successful transfer of techniques to at-risks species.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Consequently, there has been a historical gap between the study of cryopreservation technologies and its applications for wildlife conservation (reviewed in Holt, 2008;Jewgenow, Braun, Dehnhard, Zahmel, & Goeritz, 2017). While gamete cryopreservation studies regularly cite their potential use for species conservation, few have shown the successful transfer of techniques to at-risks species.…”
Section: Discussionmentioning
confidence: 99%
“…Within the field of ex situ conservation, germplasm cryopreservation has been repeatedly suggested as a new and important tool to for species conservation (Ballou, 1992;Jewgenow et al, 2017;Martinez-Paramo et al, 2017). Within the field of ex situ conservation, germplasm cryopreservation has been repeatedly suggested as a new and important tool to for species conservation (Ballou, 1992;Jewgenow et al, 2017;Martinez-Paramo et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Π’ настоящСС врСмя для сохранСния гСнСтичСского Ρ€Π°Π·Π½ΠΎ-образия Π΄ΠΈΠΊΠΈΡ… кошСк ex situ ΠΈΡΠΏΠΎΠ»ΡŒΠ·ΡƒΡŽΡ‚ΡΡ ΠΊΠ°ΠΊ Ρ‚Ρ€Π°Π΄ΠΈΡ†ΠΈΠΎΠ½-Π½Ρ‹Π΅ ΠΏΠΎΠ΄Ρ…ΠΎΠ΄Ρ‹, Ρ‚Π°ΠΊ ΠΈ Π±ΠΎΠ»Π΅Π΅ соврСмСнныС ΠΌΠ΅Ρ‚ΠΎΠ΄Ρ‹, Π½Π°ΠΏΡ€ΠΈΠΌΠ΅Ρ€ созданиС ΠΊΡ€ΠΈΠΎΠ±Π°Π½ΠΊΠΎΠ² гСнСтичСских рСсурсов (Comizzoli et al, 2009;Амстиславский ΠΈ Π΄Ρ€., 2015Jewgenow et al, 2017). CСмя 27 Π²ΠΈΠ΄ΠΎΠ²/ΠΏΠΎΠ΄Π²ΠΈΠ΄ΠΎΠ² Π΄ΠΈΠΊΠΈΡ… ΠΊΠΎΡˆΠ°Ρ‡ΡŒΠΈΡ… Π±Ρ‹Π»ΠΎ ΡƒΡΠΏΠ΅ΡˆΠ½ΠΎ криоконсСрвировано хотя Π±Ρ‹ ΠΎΠ΄ΠΈΠ½ Ρ€Π°Π·; ΠΏΠΎ Π΄Ρ€ΡƒΠ³ΠΈΠΌ прСдставитСлям сСмСйства ΠΊΠΎΡˆΠ°Ρ‡ΡŒΠΈΡ… Π΄Π°Π½Π½Ρ‹Π΅ ΠΏΠΎ Π·Π°ΠΌΠΎΡ€Π°ΠΆΠΈΠ²Π°Π½ΠΈΡŽ сСмСни Π² Π»ΠΈΡ‚Π΅Ρ€Π°Ρ‚ΡƒΡ€Π΅ ΠΎΡ‚ΡΡƒΡ‚ΡΡ‚Π²ΡƒΡŽΡ‚ (Fickel et al, 2007;Амстиславский ΠΈ Π΄Ρ€., 2017).…”
Section: Domestic Cat (Felis Silvestris Catus)unclassified